Relationship Analysis between Listener Face Direction and Utterance in Group Discussion (International Conference on Computers in Education, 2022)
The authors analyzed the relationship between face direction and utterance during group discussion. For groups of six students, face direction data were collected using video and OpenFace, and utterance data were collected using a microphone array and the Hylable system. The results of the analysis show that the average number of persons who turned their faces differed significantly when the speaker did or did not speak.